Burden of chronic spontaneous urticaria relative to atopic dermatitis and psoriasis in the United States - Weily Soong; Dhaval Patil; Jonathan Rodrigues; Ravneet K. Kohli; Kathryn Krupsky; Shaloo Gupta; Bridget L. Balkaran; Maria-Magdalena Balp (Journal of Dermatological Treatment)
Purpose To evaluate the burden of chronic spontaneous urticaria (CSU) compared with atopic dermatitis (AD) and psoriasis (PSO).Methods This retrospective, cross-sectional study used real-world data from adult respondents from the 2019 US National Health and Wellness Survey (NHWS). Outcome measures included the 36-item Short-Form Survey version 2 (SF-36v2; mental and physical component summary [MCS and PCS] scores), Work Productivity and Activity Impairment (WPAI), and healthcare resource utilization (HCRU).Results Among 74,994 respondents (CSU N = 371; AD N = 549; PSO N = 2061), mean (standard deviation [SD]) age at data collection was 41.7 (14.0), 48.4 (16.3), and 51.4 (16.6) years for CSU, AD, and PSO, respectively. Mean (standard error [SE]) MCS and PCS scores were lower (worse) among respondents with physician-diagnosed CSU vs. AD and PSO, respectively: MCS: 41.3 (0.6) vs. 44.8 (0.5) vs. 45.3 (0.2); PCS: 42.1 (0.5) vs. 47.8 (0.4) vs. 47.7 (0.2); all p < 0.001. Respondents with CSU reported higher (p < 0.001) work and activity impairment and HCRU vs. respondents with AD or PSO.Conclusion After adjusting for confounders, respondents with CSU experienced higher humanistic and economic burden compared with respondents with AD or PSO, indicating a need for new treatments and improved clinical management.